2006
DOI: 10.1002/uog.3862
|View full text |Cite
|
Sign up to set email alerts
|

Imperforate anus: a relatively common anomaly rarely diagnosed prenatally

Abstract: Objective Despite the relatively common occurrence of imperforate anus, prenatal diagnosis is rarely reported. In this study, we investigated the presence and diagnosis of imperforate anus along with strategies for improving prenatal diagnosis of the condition. Patients and methods Fetuses and infants with imper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 37 publications
3
51
0
6
Order By: Relevance
“…Anorectal atresia (ARA) is a relatively common congenital malformation that is usually diagnosed by perineal inspection after birth 1 . HDlive is a new surface-rendering mode in ultrasound imaging which uses an adjustable light source to increase depth perception 2,3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anorectal atresia (ARA) is a relatively common congenital malformation that is usually diagnosed by perineal inspection after birth 1 . HDlive is a new surface-rendering mode in ultrasound imaging which uses an adjustable light source to increase depth perception 2,3 .…”
mentioning
confidence: 99%
“…Prenatal diagnosis of ARA is rare, with only 15.9% of cases diagnosed because it relies on non-specific signs, such as an abnormally dilated distal bowel or rectum, or calcified intraluminal meconium 1 . Previous reports have highlighted the usefulness of 2D ultrasound in demonstrating absence of fetal PAMC in cases of ARA 4,5 .…”
mentioning
confidence: 99%
“…Geçmişte anorektal atrezi tanısı, kolon dilatasyonu veya kalsifiye mekonyum gibi indirekt bulgulara dayandığından prenatal saptanma oranı %8 ile %16 arasında [18,19] bildirilirken gü-nümüzde yüksek rezolüsyonlu US cihazlarının kullanımı ile fetal perinenin ayrıntılı incelenmesi sonucunda oldukça başarılı sonuçlar elde edilmeye başlanmıştır [20][21][22]. Ultrasonografide aksiyel planda normal anal sfinkter, anal kanal mukozasına ait hiperekojen halka ve çevresinde hipokoik perianal muskuler kompleksten oluşan "hedef işareti" görünümü verir (Resim 5).…”
Section: Anorektal Atrezilerunclassified
“…13 Brantberg et al reported 69 cases with imperforate anus with only 11 (15.9%) cases diagnosed or strongly suspected prenatally, at a median gestational age of 18 1 4 weeks. 12 Three of these 11 cases were isolated anal atresia without additional anomalies and, in two fetuses, intraluminal calcifications were seen. Therefore, the diagnosis of imperforate anus without rectourethral fistula is very difficult.…”
mentioning
confidence: 97%
“…12 Anderson et al were the first to report the use of prenatal US to identify intraluminal calcifications and to differentiate between enterolithiasis and meconium peritonitis. 13 Brantberg et al reported 69 cases with imperforate anus with only 11 (15.9%) cases diagnosed or strongly suspected prenatally, at a median gestational age of 18 1 4 weeks.…”
mentioning
confidence: 98%